Association between comorbid conditions and BADL/IADL disability in hypertension patients over age 45: Based on the China health and retirement longitudinal study (CHARLS). Issue 31 (August 2016) - Qian, Jiahui; Ren, Xiaohui
Abstract : Abstract: Hypertension usually coexists with other chronic conditions and can cause disability in relation to activities of daily living. We examined the association between the number and categories of comorbid conditions and disability affecting activities of daily living in hypertension patients. The data were collected from the 2013 follow-up survey of the China Health and Retirement Longitudinal Study (CHARLS), which contains information about chronic conditions and disability. Additionally, socio-demographic characteristics of 3754 hypertension patients aged 45 and older were included in this study. Comorbid conditions included dyslipidemia, stroke, and 12 other chronic conditions. Disability in relation to activities of daily living was assessed using the basic activities of daily living (BADL) and the instrumental activities of daily living (IADL) instruments. Differences in BADL/IADL disability among patients with different comorbid conditions were compared using the chi-square test, and the influence of chronic conditions and socio-demographic characteristics on BADL/IADL disability was analyzed using logistic models. Without considering the influence of specific chronic conditions on BADL/IADL, hypertension patients with additional comorbid conditions were more likely to suffer from BADL/IADL disability. When considering the effect of specific chronic conditions, the number of comorbid conditions did not significantly influence BADL/IADL disability. Dyslipidemia, chronic lung disease, stroke, memory-related diseases, and arthritis/rheumatism were associated with BADL disability. Chronic lung diseases, heart diseases, stroke, stomach/digestive system diseases, emotional/nervous/psychiatric problems, memory-related diseases, arthritis/rheumatism, and asthma were associated with IADL disability. Additionally, female, people with lower education level, people living in village, and people living in middle and western China were more likely suffer from BADL/IADL disability. Comorbid conditions were associated with disability in activities of daily living in hypertension patients aged 45 and older. The specific comorbid conditions had a stronger effect on disability in activities of daily living than the number of comorbid conditions. In addition, we should pay attention to socioeconomic factors related to disability.